The Role of the Investment Alert Task Force as a Form of Consumer Protection Against Fraudulent Investments - Pakpahan, Elvira Fitriyani; Hulu, Angellina Livonaria; Purba, Emmerita; Siregar, Jenni Yustina (Fakultas Syariah INSURI Ponorogo, 2024)
This research delves into the function of the task force in bringing attention to questionable investments via consumer protection measures, particularly in cases when several individuals fall prey to fraud resulting from these questionable investments. The major foundation for integrating and improving law enforcement in the consumer protection sector is Law No. 8 of 1999 regulating consumer protection, which regulates consumer protection. The normative juridical approach, based on deductive inquiry that begins with the examination of legislative items, is the basis of this investigation. The foundational law for Indonesian investment rules is Law no. 25 of 2007, which addresses capital investment. The notion of